2016
DOI: 10.1007/s12034-016-1231-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis and characterization of pure Co2B nanocrystals

Abstract: Cobalt boride (Co 2 B) is a significant transition metal boride having a wide range of usage area due to its high oxidation, abrasion and corrosion resistance as well as its superior electrochemical, magnetic and anisotropic properties. In this study, pure Co 2 B nanocrystals were synthesized with Co, B 2 O 3 and Mg as starting materials via the mechanochemical synthesis (MCS) method by high-energy planetary ball mill in a hardened steel vial with hardened steel balls. All the experiments were conducted under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Furthermore, diffraction peaks from impurities are not detected, suggesting high crystal purities for these Co x B catalysts. SEM images (Figure e–g) show that the as-prepared Co x B catalysts exhibit particle-like shapes, with sizes ranging from several hundreds of nanometers, as confirmed by low-magnification TEM images (insets in Figure a–c) …”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, diffraction peaks from impurities are not detected, suggesting high crystal purities for these Co x B catalysts. SEM images (Figure e–g) show that the as-prepared Co x B catalysts exhibit particle-like shapes, with sizes ranging from several hundreds of nanometers, as confirmed by low-magnification TEM images (insets in Figure a–c) …”
Section: Resultsmentioning
confidence: 55%
“…SEM images (Figure 1e−g) show that the as-prepared Co x B catalysts exhibit particle-like shapes, with sizes ranging from several hundreds of nanometers, as confirmed by lowmagnification TEM images (insets in Figure 2a−c). 40 HRTEM images taken from the regions highlighted by the red circles in the low-magnification TEM images display clear lattice fringes, as shown in Figure 2a−c, revealing the crystalline nature of all the Co x B catalysts. The detailed measurements for the adjacent lattice spacings in these HRTEM images confirm the crystal structures of these Co x B catalysts.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…Simsek et al [15] reported that Co 2 B particles with particle sizes ranging between 30-100 nm were produced by chemical reduction. Baris et al [33] succeeded in producing nanocrystalline Co 2 B particles with a crystal size of approximately 10 nm by mechanochemical method using Co, B 2 O 3 and Mg. Kartal [16] produced Co 2 B particles calciothermically in molten salt medium starting from CoO and B 2 O 3 and stated that the particle sizes are very variable but above 10 microns.…”
Section: Effect Of Process Duration On Co X B Particlesmentioning
confidence: 99%
“…Kartal [16] reported the saturation magnetisation, coercivity and permanence values of the particles produced calciothermically starting from B 2 O 3 and CoO as 30.107 emu/g, 40.210 Oe, 0.764 emu/g, respectively. Baris et al [33] found that the saturation magnetisation values of the particles produced magnesiothermically using Co and B 2 O 3 varied between 35 and 50 emu/g. Şimşek et al [15] observed that the saturation magnetisation values of the particles produced by chemical reduction with the use of high purity starting materials varied between 19 and 68.5 emu/g depending on the calcination medium.…”
Section: Effect Of Process Duration On Co X B Particlesmentioning
confidence: 99%
“…Conventional method for the synthesis of transition metal borides uses elemental powders and high temperature and/or pressures (e.g. higher than 2500 °C via arc melting) or a chemical or physical method which proves impractical to produce such material in nanoscale [1,2,[34][35][36]. Previous studies, have reported the formation of various species of boron oxide encapsulating the synthesized crystalline core particles [8,34].…”
Section: Introductionmentioning
confidence: 99%